1998
DOI: 10.1074/jbc.273.34.21658
|View full text |Cite
|
Sign up to set email alerts
|

Asparagine-linked Oligosaccharides Are Localized to a Luminal Hydrophilic Loop in Human Glucose-6-Phosphatase

Abstract: Deficiency of glucose-6-phosphatase (G6Pase), an endoplasmic reticulum transmembrane glycoprotein, causes glycogen storage disease type 1a. We have recently shown that human G6Pase contains an odd number of transmembrane segments, supporting a ninetransmembrane helical model for this enzyme. Sequence analysis predicts the presence of three potential asparagine (N) with an Ala (N96A) moderately reduced enzymatic activity and had no effect on G6Pase synthesis or degradation, suggesting that oligosaccharide chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 21 publications
3
41
0
Order By: Relevance
“…The nucleotide sequence in all constructs was verified by DNA sequencing. D38V-3Ј-FLAG and P178S-3Ј-FLAG mutants have been described previously (19).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The nucleotide sequence in all constructs was verified by DNA sequencing. D38V-3Ј-FLAG and P178S-3Ј-FLAG mutants have been described previously (19).…”
Section: Methodsmentioning
confidence: 99%
“…In the presence of a glycosylation inhibitor, tunicamycin (32), only the 37-kDa nonglycosylated G6Pase was detected, confirming their identities. We have previously shown that both forms of G6Pase are enzymatically active and that the nonglycosylated G6Pase retains ϳ40% activity (19). Immunoblot analyses showed that the active site mutants, K76N, R83C, R83H, H119L, and R170Q (Fig.…”
Section: Mutations Identified In the G6pasementioning
confidence: 99%
See 3 more Smart Citations